Dosimetric study of sediments at the beta dose rate scale: Characterization and modelization with the DosiVox software. (October 2015) - Martin, Loïc; Mercier, Norbert; Incerti, Sébastien; Lefrais, Yannick; Pecheyran, Christophe; Guérin, Guillaume; Jarry, Marc; Bruxelles, Laurent; Bon, François; Pallier, Céline
Abstract: The effects of sediment heterogeneity on beta dose rate have been investigated by simulation with the DosiVox software. Basic sediment cases, as well as a model of a micro-stratified sediment from the Mas d'Azil cave have been modeled at a few centimeters scale. The results of the simulations have highlighted different factors having a significant impact on the beta dose rate dispersion, among which the heterogeneity of the radioactive elements, the distribution of grains in the matrix and their proportion in the sample. These factors contribute to enlarge beta dose distributions and even create complex ones, and inevitably induce errors in the dating process. These effects are discussed, as well as the potential of the simulation to calculate beta dose rates in sediment samples and the necessity of using sampling protocols adapted to sediment complexity. Highlights: The DosiVox software allows calculating beta dose rates at the grain size level. A micro-stratified sediment is characterized and a model created. Factors inducing significant micro-dosimetric effects are identified. The spatial distribution of grains and/or radioelements are critical factors.